Design and Testing of Belt Grinding Development - Setiawan, Sepdirama; K, Arwizet; Syahri, Budi; Ambiyar, Ambiyar; Darmawi, Darmawi; A, Yufrizal (Teknomekanik, 2018)
The author observes that the use of belt grinding is still rare in the writer's own environment, both in the fields of education and small industries, because there are still many people who are fixated on ordinary grinders, and think that ordinary grinders are better in all work. The development of belt grinders has changed people's perspectives through the development that the authors have done, with increasing belt grinding functions through development which will certainly make belt grinders even more useful. This belt burrs are made and developed through pre-existing belt grinding shapes. The result of this development is a belt grinder which has a function more than the belt grinder which is already before. This belt burrs has three types of work functions, namely vertical, horizontal, and cutter, and also features speed control. With the development that the author does, of course, it will change people's perspectives because belt grinding has a function that is better than before and can better help the work of a grinding process.